Study on Crack Resistance Mechanism of Helical Carbon Nanotubes in Nanocomposites - Zhiwu Bie; Xuefeng Liu; Yajie Deng; Xian Shi; Xiaoqiao He (Nanomaterials)
Helical carbon nanotubes (HCNTs) with different geometrical properties were constructed and incorporated into nanocomposites for the investigation of the anti-crack mechanism. The interfacial mechanical properties of the nanocomposites reinforced with straight carbon nanotubes and various types of HCNTs were investigated through the pullout of HCNTs in the crack propagation using molecular dynamics (MD). The results show that the pullout force of HCNTs is much higher than that of CNTs because the physical interlock between HCNTs and matrices is much stronger than the van der Waals (vdW) interactions between CNTs and matrices. Remarkably, HCNTs with a large pitch length can not only effectively prevent the initiation of breakages but also hinder the growth of cracks, while HCNTs with a small diameter and tube radius cannot even effectively prevent the initiation of cracks, which is similar to straight CNTs. Moreover, the shear resistance of HCNTs increases with the increase in the helix angle, which remains at a high level when the helix angle reaches the critical value. However, HCNTs with a small helix angle and large diameter can carry out more polymer chains, while snake-like HCNTs and HCNTs with a small diameter and helix angle can hardly carry out any polymer chain during the pullout process and show similar interfacial properties to the straight CNTs.